SEJARAH TEORI HUKUM ISLAM SYIAH ZAIDIYAH - Maswir, Maswir (Al-Qawaid : Journal of Islamic Family Law, 2024)
This research was motivated by differences of opinion among friends about who willreplace the leadership after the death of the Prophet Muhammad, in part Most of theCompanions agreed and pledged allegiance to Abu Bakr as the first caliph, and Others are ofthe opinion that the rightful person to be caliph is Ali bin Abi Talib That was the starting point ofthe birth of the Shiite group, namely the group of followers and supporters of Ali bin Abi Talib.This article aims to find out the biography of Zaid Bin Ali Zainul Abidin Bin Husain andthe development of Shia Zaidiyah, to know the theory of Shia Zaidiyah Islamic law and to knowthe views of Shia Zaidiyah. This research is a descriptive qualitative type of research. Thisresearch requires two methods of data collection techniques, namely how to document and howto study literature.This research states that the Zaidivah svi'ah is a Shi'ite sect that attributes its madhhab toZain bi Ali Zainal Abidin who was the son of Zainal Abidin. Looking at the explanation above, itcan be said that the Zaidiyah Shi'ah sect is the Shi'ah that is closest in understanding to the Ahlsunnah wal jama ah. In its development, this madhhab actually existed after Zaid bin Ali died.Then the madhhab was developed by the followers of Zaid bin Ali and compiled its own book,especially in matters of fiqh and hadith issues, which was called the Majmu Al-Kabir book. Untilnow, the Zaidivah svi'ah still exists, especially in North Yemen, because it is known that themajority of the North Yemeni population adheres to the Shi'a Zaidivah school of thought.Regarding the theory of Islamic law in the Zaidiyah madzhab, as has been explained, the manhajof the Zaidiyah madzhab is not too far from the ahl sunnah wal jamaah. In the order of manhaj,the istinbath method, the law of the Zaidiyah school still positions the Qur'an as the first sourceand then the sunnah, ijma, qiyas and reason.